Copyright protection of works generated by artificial intelligence in the european copyright law: between indirect and tailored protection - Palmela Fidalgo, Vítor; Antunes, Diogo (Actas de Derecho Industrial, 2021)
Amid the 4th Industrial Revolution, Artificial Intelligence (AI) systems are developing to a point where they will cease to be solely a tool for human beings. We are witnessing, every day, the emergence of more and more works that do not have any human intervention, and it is estimated that before long, the primary cultural source of new works may move from the human to the machine. The purpose of this study is to frame the current debate on the intellectual protection of works generated by AI systems and how to understand the legal options for their protection by copyright or related rights.